EFEKTIVITAS ANTIMIKROBA BUAH LAKUM (Cayratia trifolia [L.] DOMIN) TERHADAP PERTUMBUHAN BAKTERI Streptococcus sp. (L.10.3) - Yuniar, Helenda Ferni Asri; Rahmawati, Rahmawati; Rousdy, Diah Wulandari (Universitas Tanjungpura, 2020)
Streptococcus sp. (L.10.3) is one of the bacteria that can cause dental plaque. This study was aimed to determine the antimicrobial activity of the fraction of methanol fraction of fruit against Streptococcus sp. (L.10.3). This study used a Completely Randomized Design (CRD), 3 levels of concentrations of fraction methanol fraction 0.3 g/mL, 0.6 g/mL and 0.9 g/mL and 2 positive control treatments of amoxicillin and negative control using distilled water with three times repeated. Testing the antibacterial activity using the Kirby-Bauer method using disc paper. The results of the study showed the average diameter of inhibition zones of Streptococcus sp. (L.10.3) in the 24th hour incubation ranged from 7.70-10.72 mm and in the 48th hour incubation ranged from 8.70-10.37 mm. A concentration of 0.9 g/mL is an effective concentration with a moderate inhibition response category. Giving fraction of methanol fraction of fruit at the lowest concentration of 0.3 g/mL is able to provide a moderate inhibition response with the bacteriocidal antibacterial category.